Studi Penggunaan Obat pada Pasien Gastroesophageal Reflux Disease (GERD) Rawat Jalan di RS. Aura Syifa Kediri Periode Januari - November 2022 - Fitria Wahyuning Wulan; Mellinnia Lailla Sari (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: Gastroesophageal Reflux Disease (GERD) is a pathological condition caused by reflux of contents from the stomach entering the esophagus, with various signs and symptoms involving the esophagus, pharynx, larynx and airway. Gastroesophageal Reflux Disease (GERD) has typical symptoms of heartburn and regurgitation. So that the symptoms that appear will interfere with all activities carried out by someone. Objective: This study is to determine the profile picture of drug use in outpatient Gastroesophageal Reflux Disease (GERD) patients at Aura Syifa Hospital Kediri and to determine the study of drug use in outpatient Gastroesophageal Reflux Disease (GERD) patients at Aura Syifa Hospital Kediri by analyzing the right indications and right doses. Method: This study is a descriptive observational study with retrospective data collection from patient medical record data. Results: The results of a study on the useof drugs in outpatient gastroesophageal reflux disease (GERD) patients at Aura Syifa Hospital Kediri for the period January-November 2022 by analyzing the right indications and correct doses, which were obtained as many as 175 patients. The most GERD patients were women as many as 114 patients and men as many as 61 patients. The most common age for GERD is 56-65 years old and >65 years old. The most widely used drug class is the Proton Pump Inhibitor (PPI) class with a percentage of 38% and the drug in this class that is often used is lansoprazole with 167 prescriptions. The results of a study on drug use in outpatient gastroesophageal reflux disease (GERD) patients at Aura Syifa Hospital Kediri for the period January- November 2022 that meet the rationality of treatment based on the literature of the Indonesian GERD Consensus in 2013 or BNF 2017 or Pharmacotherapy A Pathophysiologic Approach 11th edition in 2020 or Medscape, where the indication is 100% (175 patients) and the right dose is 100% (175 patients).